A case of Takayasu‘s aortoarteritis with severe dilated cardiomyopathy in pregnancy - Satia, Meena; Ganapathi, Trupthi; Panchbudhe, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Takayasu’s aortoarteritis (TA) is a idiopathic, rare, chronic, giant-cell inflammatory disease of the arteries which primarily involves the aorta, its main branches and coronary and pulmonary arteries Women are affected in 80–90% of cases with a mean age of presentation in the second and third decade of life, reflected in a synonym for TA as ‘‘young female arteritis’’. Also known as pulse less disease that causes progressive damage including inflammation, scarring, narrowing and abnormal ballooning inside the wall of aorta and major arteries. A pregnancy in such cases is often associated with severe life-threatening complications and is hazardous to the life of the mother and therefore requires contraception counseling. Our case is a coexistence of Takayasu’s aortoarteritis and dilated cardiomyopathy which is an uncommon complication of TA and hence required termination of pregnancy.